Titanic : a fresh look at the evidence by a former Chief Inspector of Marine Accidents - Lang, John S. (Rowman and Littlefield Publishers, 2012)
Publisher description: The sinking of the Titanic on her maiden voyage in April 1912 was one of the defining moments of the twentieth century. Books and films about the disaster that befell the iconic liner are commonplace, and it seems almost inconceivable that anything fresh can emerge. But there is one angle that has not been covered. John Lang, who was for five years the UK's Chief Inspector of Marine Accidents, presents the circumstances surrounding the loss of the Titanic through the eyes of a professional marine accident investigator. He has examined the original evidence and worked his way through the confusing, conflicting and often incoherent testimonials given at the two original inquires. He brings the standards of a twenty-first-century accident investigation to bear on the events of April 1912, using his expertise and his investigator's instinct to determine exactly what happened a century ago - and why. His unique approach reveals some surprising findings.